HBJ school dictionary. - Harcourt Brace Jovanovich (Orlando, FL : Harcourt Brace Jovanovich, 1990)
A dictionary for use by students in intermediate grades.
Keywords: English language -- Dictionaries, Juvenile; English language -- Dictionaries